2019
DOI: 10.1186/s13028-019-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic reference intervals of Danish sows at mid-gestation

Abstract: Hematologic reference intervals are useful tools for interpretation of laboratory results in swine practice and research. Until now, there were no hematologic reference intervals established for gestating Danish sows and those established in other countries are either out-dated, produced using very few sows or incomplete with few variables. In the past few decades there have been significant increases in litter size due to breeding, as well as the development of new analytical procedures for hematology and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
1
16
1
2
Order By: Relevance
“…Previously, we have established that the reference interval of HbC for mid-gestation Danish sows lies between 103 and 145 g/L [7]. We observed an average HbC of 106.9 g/L in the current study which is at the lower side of the established reference interval.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Previously, we have established that the reference interval of HbC for mid-gestation Danish sows lies between 103 and 145 g/L [7]. We observed an average HbC of 106.9 g/L in the current study which is at the lower side of the established reference interval.…”
Section: Resultssupporting
confidence: 59%
“…The sows were divided into two categories based on their HbC, anemic (HbC < 103 g/L) and non-anemic (HbC ≥ 103 g/L). The cut off value for anemia was based on our recent study on reference intervals for sows [7].…”
Section: Resultsmentioning
confidence: 99%
“…The hematologic RIs obtained in this study are different from those previously reported in the literature, probably because those studies were developed in different experimental models of pigs and did not differentiate results according to the productive stage, BC or age [1,4,6,7,8,18]. Due to the evidence existence of factors like physiological state, weight can vary hematological values, we now propose new hematological RIs for sows, based on productive stage.…”
Section: Discussioncontrasting
confidence: 66%
“…The sows in our study probably were not iron deficient enough to present microcytic erythrocytes and to respond to treatment. The average baseline HbC in FeT and FeC sows were within the reference limits for sows at mid-gestation [21]. A study in piglets has shown that animals with high HbC (> 100 g/L for a day old piglet) respond less to treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…It was further characterized as hypochromic (MCHC < 18.37 mmol/L), normochromic (MCHC ≥ 18.37 ≤ 20.31 mmol/L) and hyperchromic (MCHC > 20.31 mmol/L). These cut off values were chosen based on our recent study on reference intervals for Danish sows at mid-gestation [21]. A sow was considered to be suffering from iron deficiency anemia (IDA) when HbC, MCV and MCHC values were below the lower limits of all these reference intervals.…”
Section: Methodsmentioning
confidence: 99%